The mediating functions of coping strategies for the relationship between the loss of personal resources during COVID-19 and the providing support to students: The differences between believing and non-believing teachers in Poland - Krzysztof Jurek; Iwona Niewiadomska; Joanna Chwaszcz; Monika Dobrogowska (PLoS ONE, 2025)
Introduction The teaching profession is not only related to the transmission of knowledge and the formation of attitudes in alumni, but also to the provision of multidimensional support to students in difficult/problematic situations. Social support refers to the provision of psychological and material resources by the social network to enhance the individual’s capacity to cope with stress. Aim The aim of this article is to present the mediating functions of stress coping strategies for the relationships occurring between the severity of stress generated by losses in personal resources during the COVID-19 pandemic and providing support to students in believing and non-believing teachers. Methods The nationwide and representative study was conducted from September 13, 2021 to October 1, 2021. The study included a total of 2500 teachers. The mean age was 43.93 years (SD = 9.89). The Polish adaptation of Hobfoll’s Conservation of Resources-Evaluation (COR-E), the Inventory for Measuring Coping with Stress (MINI-COPE) and The Berlin Social Support Scales (BSSS) were employed in the research. Results There are statistically significant differences between believing and non-believing teachers in the mediating functions of stress coping strategies for the relationship between the perception of personal losses and the providing support to students. Teachers’ religiosity promotes greater flexibility in the use of coping strategies in the process of coping with chronic stress compared to non-believing teachers. Conclusion The results presented justify the postulate that teachers should benefit from various forms of support to counteract personal losses, including support of a religious nature.